Present and future of anaesthesiology - Mellin-Olsen, Jannicke (Acta medica Lituanica, 2012)
The aim of the European Union of Medical Specialists is to improve and harmonise training and free movement of medical specialists in Europe. The training of European anaesthesiologists varies across country borders. The Section and Board of Anaesthesiology has chaired the development of new training guidelines and curriculum which will serve to make the training more uniform. We have also been pioneers in patient safety and in developing our specialty with its various areas of competence. We need to take charge of our own future, also when it comes to manpower and medical development.
Keywords: patient safety; post-graduate training; examination; migration